Isotopic Tracing of Thallium Contamination in Soils Affected by Emissions from Coal-Fired Power Plants - Vaněk, Aleš; Grösslová, Zuzana; Mihaljevič, Martin; Trubač, Jakub; Ettler, Vojtěch; Teper, Leslaw; Cabala, Jerzy; Rohovec, Jan; Zádorová, Tereza; Penížek, Vít; Pavlů, Lenka; Holubík, Ondřej; et al. (Environmental science & technology, 2016)
Here, for the first time, we report the thallium (Tl) isotope record in moderately contaminated soils with contrasting land management (forest and meadow soils), which have been affected by emissions from coal-fired power plants. Our findings clearly demonstrate that Tl of anthropogenic (high-temperature) origin with light isotope composition was deposited onto the studied soils, where heavier Tl (ε(205)Tl ∼ -1) naturally occurs. The results show a positive linear relationship (R(2) = 0.71) between 1/Tl and the isotope record, as determined for all the soils and bedrocks, also indicative of binary Tl mixing between two dominant reservoirs. We also identified significant Tl isotope variations within the products from coal combustion and thermo-desorption experiments with local Tl-rich coal pyrite. Bottom ash exhibited the heaviest Tl isotope composition (ε(205)Tl ∼ 0), followed by fly ash (ε(205)Tl between -2.5 and -2.8) and volatile Tl fractions (ε(205)Tl between -6.2 and -10.3), suggesting partial Tl isotope fractionations. Despite the evident role of soil processes in the isotope redistributions, we demonstrate that Tl contamination can be traced in soils and propose that the isotope data represent a possible tool to aid our understanding of postdepositional Tl dynamics in surface environments for the future.
Keywords: Environmental Monitoring; elektrárny; látky znečišťující půdu; Soil Pollutants; Thallium; monitorování životního prostředí; půda; Soil; thallium; uhlí; Power Plants; Coal